Grumpier old men [videorecording (DVD)] - Lemmon, Jack; Matthau, Walter; Ann-Margret, 1941-; Loren, Sophia, 1934-; Pollak, Kevin, 1958-; Hannah, Daryl (Warner Home Video, 1997)
Max and John team up against Maria who has turned their favorite bait shop into an Italian restaurant.